Marathon : the pursuit of the Presidency, 1972-1976 - Witcover, Jules (New York : Viking Press, 1977)
Examines the 1976 presidential campaign from its beginnings in 1972 through the election of Jimmie Carter.
The end of the marathon. The ultimate media event -- How we got here. From elitist to mass politics -- Jockeying for position : the Republicans. The serendipitous Gerald Ford ; Ford the candidate ; Ronald Reagan begins to stir ; ford faces reality ; Reagan plunges in -- Jockeying for position : the Democrats. The stirrings of Jimmy Carter ; The "inevitability" of Teddy Kennedy ; Carter adjusts his plans ; The rush to fill the liberal void ; The field on the right ; Wishful thinkers -- The delegate hunt : the Democrats. Skirmishing ; Early caucuses ; One-on-one politics in New Hampshire ; Massachusetts : enter Jackson and Wallace ; The demise of George Wallace ; The bad luck of Mo Udall ; The demise of Scoop Jackson ; A breakthrough, and a breach ; The new challengers ; The resistance crumbles -- The Democratic convention. Unity, and Fritz Mondale -- The delegate hunt : the Republicans. New Hampshire : Reagan's [ninety]-billion problem ; Ford pours it on ; The Reagan comeback ; The Ford recovery ; Loose ends and uncommitted ; The battle of Mississippi ; The Schweiker affair -- The Republican convention. A surprise strategy ; Mississippi again ; The selection of Bob Dole -- Getting ready. The Carter battle plan ; The Ford battle plan -- The fall campaign. Carter's shaky start ; Playboy, and the first debate ; Trouble for Ford ; The second debate : Eastern Europe ; Accentuating the negative ; Down to the wire -- Conclusion. New president, old system.
Includes index.
Keywords: 1969-1977; 1970-1980.; Presidents -- United States -- Election -- 1976.; z -- y; 15.85 history of America; Politics and government; Presidents -- Election; Election campagnes; Presidential candidates; Presidents -- United States -- Election -- 1976.; Presidents -- United States -- Election -- 1976.; United States -- Politics and government -- 1969-1974.; United States -- Politics and government -- 1974-1977.; United States -- Politics and government -- 1969-1974.; United States -- Politics and government -- 1974-1977.; EE. UU. -- y; EE. UU. -- y; x; x; United States; United States; United States -- Politics and government -- 1969-1974.; United States -- Politics and government -- 1974-1977.; United States -- Politics and government -- 1974-1977.; United States -- Politics and government -- 1961-1974.